Integrated multitrophic culture of shrimp Litopenaeus vannamei and tilapia Oreochromis niloticus in biofloc system: A pilot scale study - Holanda, Mariana; Ravagnan, Elisa; Lara, Gabriele; Santana, Gabriel; Furtado, Plinio; Cardozo, Alessandro; Wasielesky, Wilson; Poersch, Luis Henrique (Frontiers in Marine Science, 2023)
The present study aimed to evaluate two stocking densities of tilapia in an integrated culture with shrimp Litopenaeus vannamei reared in a pilot-scale biofloc system. Two stocking densities of tilapia were tested, 35 and 65 fish m-3 in a recirculating system with 10 m³ tanks for shrimp culture and 4 m³ for tilapia culture with water recirculation of 965.66 ± 92.83 L h-1 during 78 days. The initial weight of shrimp was 0.9±0.1 g and of tilapia was 7.1±3.2 g. Shrimps were fed according to the feeding table and fish were underfed to stimulate bioflocs consumption. Tilapia densities did not affect shrimp growth (11.5±1.9 g and 10.1±0.7 g for 35 and 65 fish m-3 treatments, respectively). The tilapia presented a FCR lower than 1, proving that bioflocs were consumed by fish. The clarification time was shorter when compared to other studies with shrimp monoculture. Between the treatments, a reduction of 10 hours in the system clarification occurred when lower fish stocking density was used. The results demonstrate the feasibility of integrated shrimp and tilapia culture on a pilot scale, without compromising shrimp productivity.